Scenario Of Solid Waste Management In Hetauda Municipality, Nepal - Neupane, Bigyan; Neupane, Shuvee (International Journal of Environment, 2013)
The paper aims to enlighten the solid waste management of Hetauda Municipality in Makwanpur district of an area of 44.5 sq. km. The total human population of the municipality is 84,671 (CBS 2011). Out of 11 wards, 5 wards (1, 2, 3, 4 and 10) were selected for the present study. In total 50 households, 10 institutions and 10 commercial sectors were selected from studied wards from which samples of different types of wastes were collected, segregated and weighed. Weight was calculated using a digital spring balance and a bag 0.043 m3 was used for the estimation of volume. Organic wastes were found to be dominant in the household (51.73%) and commercial sectors (61.70%) whereas in institutions, plastic (50.36%) and papers (38.19%) were prevailing. The findings revealed that per capita 155.4 gm/person/day household waste was generated in Hetauda Municipality. The residents are also aware of the harmful effects of the wastes, and demand an effective solid waste management services. Though they are aware about the sustainable management of wastes, due to erratic collection of wastes, some of them throw the wastes in the open lands - The local people also participate in the awareness campaigns organized by local NGOs and municipal. Solid waste management strategies are timely need for an effective management of anthropogenic wastes. Regular waste collection, improvement of dumping sites and sufficient number of composting plants are recommended in the municipality. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 105-114 DOI: http://dx.doi.org/10.3126/ije.v2i1.9214